Over-Dependence On Oil Revenue In Nigeria: Consequences Of Covid-19 On Budgetary Allocation Of Federal Government Of Nigeria - ALI IBRAHIM ABBAS; MUSTAPHA ALHAJI ALI; SANI GARBA WAKILI (Covenant University Journal of Politics and International Affairs, 2023)
This study examines the consequences of Covid-19 pandemic on budgetary allocation of Federal Government of Nigeria in view of over-dependence on crude oil and natural gas as the major source of revenue for public service delivery. Despite the emergence of the disease in December, 2019 in China and its spread globally gradually; Nigeria recorded the first case of the disease on the 27th February, 2020. Efforts to contain the spread of Coronavirus necessitated implementing some measures that led to disruption of economic activities within and across national boundaries. Consequently, global oil prices declined and that has severely affected Nigeria as one of the producers. Nigeria’s budget with price of crude oil as the major indicator for projection becomes unrealistic for achieving the recurrent and capital expenditure components of the 2020 budget. Due to that, 2020 Appropriation Act was amended and 2021 Appropriation Bill was presented based on this economic reality. This study employed Documentary Research Method (DRM) and applied document analysis as a technique of analyzing qualitative research data. The study found that Covid-19 pandemic led to global economic meltdown which by extension responsible for Nigeria’s economic downturn characterized by declined in oil production and oil price resulting to drop in oil revenue and increasing budget deficit. Out of the 2021 federal budget of N13.08 trillion; N5.20 trillion will be financed mainly by borrowing and that can widen the budget deficit and by extension accumulation of debt. The study also established positive correlation between declined in oil price/revenue and the increasing budget deficit of the FGN. Based on this, government should sustain the economic diversification drive and implement Post Covid-19 Recovery measures such as the Economic Sustainability Plan.